A bucket of blessings - Sehgal, Kabir; Sehgal, Kabir; Tsong, Jing Jing (New York : Beach Lane Books, 2014)
It has not rained for many weeks. The village pond and well are dry. Then one-day Monkey remembers a story his mama used to tell him- a story about how peacocks can make it rain by dancing? Is Mama's story true? With an empty bucket and a hope-filled heart, Monkey sets out to see. Lushly illustrated and beautifully retold, this empowering Indian myth thinking is sure to resonate with readers of all ages.
Keywords: a -- a